Design and Implementation of Telemedicine Platform for Neurology Consultations an Agile Development Approach - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research aims to develop a telemedicine platform that can be used for neurology consultations efficiently and effectively. The development method used is Agile Development, which allows for the breaking down work into sprints that can be done iteratively. The research stages include user needs analysis, application development based on the telemedicine system architecture design, user acceptance evaluation, and final evaluation of the effectiveness of the telemedicine platform. The evaluation results showed that the platform improved the accessibility and quality of remote neurology consultation services by providing a satisfactory user experience. This research makes a significant contribution to developing a telemedicine platform for neurology consultations with a focus on user needs and the application of efficient development methodologies, which can be an effective solution in expanding the accessibility of neurology healthcare services and improving the quality of services provided by neurology doctors.